MONITORING PENDISTRIBUSIAN BANTUAN SOSIAL WARGA TERDAMPAK COVID-19 AKIBAT KEBIJAKAN PEMBATASAN SOSIAL BERSKALA BESAR - Ridhuan, Syamsu; Syah, Kaharuddin (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
AbstractThis community service is done in collaboration with colleagues from the Jakarta Islamic University, in partnership with the Provincial Government of DKI Jakarta through the work unit of the regional organization of the National Unity and Politics Agency. The initial idea, inspired by the appeal of local governments so that the community, organizations, institutions and related agencies can participate in monitoring the distribution of social assistance from the government and / or local government at the time of the implementation of the Large-Scale Social Restrictions policy, due to the Coronavirus Disease (Covid-19) pandemic. The aim is to assist the government in conducting monitoring, so that the social assistance packages available are truly in accordance with the type, quantity and quality that are prepared to be given to people affected by Covid-19 fairly and on target. The method is carried out by changing ideas into a design of monitoring activities. Location in the RW area in the neighborhood of North Utan Kayu Village, Matraman District, East Jakarta City. The steps are to coordinate with the Camat, Lurah and visit Covid-19 Command Post as a shelter for social assistance before it is distributed by RT Heads who are assisted by volunteers. The monitoring results show that the distribution of social assistance, groceries packages went smoothly, safely, and there were no problems potentially causing social unrest. Recommendations that monitoring results be used as evaluation and feedback material for program improvement. Keywords: covid-19, monitoring, social assistance AbstrakPengabdian kepada masyarakat ini dilkasanakan bekerja sama dengan kolega dari Universitas Islam Jakarta, bermitra dengan Pemerintah Provinsi DKI Jakarta melalui unit kerja organisasi perangkat daerah Badan Kesatuan Bangsa dan Politik. Ide awalnya, terinspirasi himbauan pemerintah daerah agar masyarakat, organiasi, institusi dan instansi terkait dapat berpartisipasi melakukan monitoring pendistribusian bantuan sosial dari pemerintah dan/atau pemerintah daerah pada waktu pemberlakuan kebijakan Pembatasan Sosial Berskala Besar, akibat pandemi Coronavirus Disease (Covid-19). Tujuan memabantu pemerintah melakukan pemantuan, agar paket bantuan sosial yang tersedia benar-benar sesuai dengan jenis, jumlah dan kualitas yang dipersiapkan diberikan kepada warga terdampak Covid-19 secara adil dan tepat sasaran. Metode, dilakukan dengan cara merubah ide menjadi rancangan kegiatan monitoring. Lokasi di wilayah RW dalam lingkungan Kelurahan Utan Kayu Utara, Kecamatan Matraman, Kota Jakarta Timur. Langkah-langkahnya, koordinasi dengan Camat, Lurah dan mengunjugi Posko Covid-19 sebagai tempat penampungan bantuan sosial sebelum didistribusikan oleh para Ketua RT yang dibantu relawan. Hasil monitoring menunjukkan bahwa pendistribusian bantuan sosial, paket sembako berlangsung lancar, aman, dan tidak ada masalah berpotensi menimbulkan keresahan sosial. Rekomendasi agar hasil monitoring digunakan sebagai bahan evaluasi dan feedback untuk pernyempurnaan program. Kata kunci: covid-19, monitoring, bantuan sosial